An Advanced Robust AVR-PSS Based H2 and H∞ Frequency Approachs Simulated Under a Realized GUI - Kabi Wahiba; Ghouraf Djamel Eddine; Naceri Abdellatif (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This article present a comparative study between two advanced robust frequency control strategies and their implementation using our realised Graphical User Interface ‘GUI’ under MATLAB software: the first method based on loop-shaping H∞ optimization technique and the second on robust H2 control method (LQG controller associated with KALMAN filter), and applied on automatic excitation control of synchronous generators, to improve transient stability and robustness of a single machine- infinite bus (SMIB) system operating in different several conditions. The computer simulation results (static and dynamic stability), with test of robustness against machine parameters uncertainty (electric and mechanic), have proved that good dynamic performances, showing a stable system responses almost insensitive to large parameters variations, and more robustness using robust H∞ controller in comparison with H2 approach by exploiting our developed GUI interface in this work.